Examining Public Service Motivation in Southeast Asia: Bibliometric – Content Analyses - Kurniasih, Denok; Setyoko, Paulus Israwan (Jurnal Manajemen Pelayanan Publik, 2026)
This study maps the development of Public Service Motivation (PSM) research in Southeast Asia using 63 Scopus-indexed publications from 2014 to 2024. The data were analyzed with Bibliometrix/Biblioshiny and complemented by content-oriented interpretation of the main themes in the corpus. The findings show that regional PSM research remains limited and uneven, with Vietnam and Indonesia receiving the most visible attention. Bibliometrically, the study identifies dominant authors, journals, countries, collaborations, and keyword clusters. Substantively, PSM is mainly discussed through leadership, organizational context, job crafting, work attitudes, and performance. This pattern suggests that Southeast Asian PSM research often explains motivation through organizational and managerial mechanisms rather than individual altruism alone. The study contributes by clarifying the regional structure of PSM scholarship and underexplored future research directions.